A synchrotron X‐ray diffraction deconvolution method for the measurement of residual stress in thermal barrier coatings as a function of depth. Issue 6 (24th October 2016) - Li, C.; Jacques, S. D. M.; Chen, Y.; Daisenberger, D.; Xiao, P.; Markocsan, N.; Nylen, P.; Cernik, R. J.
Abstract : The strain profile in a YZrO3 thermal barrier coating has been measured and shows possible mechanisms of in‐service failure. The method relies on deconvoluting diffraction patterns at different depths for the reflection geometry used. The nondestructive test could be applied to whole fabricated components Abstract : The average residual stress distribution as a function of depth in an air plasma‐sprayed yttria stabilized zirconia top coat used in thermal barrier coating (TBC) systems was measured using synchrotron radiation X‐ray diffraction in reflection geometry on station I15 at Diamond Light Source, UK, employing a series of incidence angles. The stress values were calculated from data deconvoluted from diffraction patterns collected at increasing depths. The stress was found to be compressive through the thickness of the TBC and a fluctuation in the trend of the stress profile was indicated in some samples. Typically this fluctuation was observed to increase from the surface to the middle of the coating, decrease a little and then increase again towards the interface. The stress at the interface region was observed to be around 300 MPa, which agrees well with the reported values. The trend of the observed residual stress was found to be related to the crack distribution in the samples, in particular a large crack propagating from the middle of the coating. The method shows promise for the development of a nondestructive test for as‐manufactured samples.